Economic Crises and Pandemics: Mitigating the Effects Through Sustainable Actions and Elements of Competitive Advantage (Global Journal of Human-Social Science, 2024)
The COVID-19 pandemic brought with it a serious economic crisis in 2020, affecting several sectors of the economy and companies extensively, especially Small and Medium Enterprises (SMEs). History shows the recurrence of economic crises with global impacts, such as the Great Depression of 1929 and the 2008 subprime crisis, as well as localized impacts, like the 2014 crisis in Brazil. Faced with the potential repetition of similar events in the future and the need to identify risk mitigation strategies for SMEs, this work aims to provide a set of guidelines based on actions related to sustainability and elements of competitive advantage that SMEs can employ to face economic crises or pandemics. Regarding the methodological aspects, this is an exploratory and descriptive research with a qualitative approach. Data were collected through documentary and bibliographical research in the scientific literature, focusing on sustainability actions and competitive advantages employable by SMEs to mitigate risks arising from economic crises and pandemics.